2011
DOI: 10.5897/ijps11.1485
|View full text |Cite
|
Sign up to set email alerts
|

Properties of high calcium wood ash and densified silica fume blended cement

Abstract: Recycling industrial waste material as construction material to minimize production of ordinary Portland cement could solve arising industrial waste management problems and increase environmental sustainability. This study focused on the incorporation of wood biomass ash in combination with silica fume in blended cement. In this study, physical and chemical properties of high calcium wood ash (HCWA) and densified silica fume (DSF) were thoroughly characterized. Results indicated that HCWA is an active hydrauli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…DSF's main field of application was as a pozzolanic material that yielded the high performance of concrete. The physical and chemical properties of DSF and OPC were mentioned earlier by authors from previous studies [18].…”
Section: Introductionmentioning
confidence: 77%
See 1 more Smart Citation
“…DSF's main field of application was as a pozzolanic material that yielded the high performance of concrete. The physical and chemical properties of DSF and OPC were mentioned earlier by authors from previous studies [18].…”
Section: Introductionmentioning
confidence: 77%
“…It was processed to enhance the bulk density by pneumatic densification. The previous author determined the physical and chemical properties of DSF studied and used in this study [18]. DSF's main field of application was as a pozzolanic material that yielded the high performance of concrete.…”
Section: Introductionmentioning
confidence: 99%
“…A new type of blended cement is produced when wood waste ash is added to the ordinary Portland cement (OPC). Cheah and Ramli [8] studied the compressive development of mortar mixes containing wood waste ash as a cement replacement. The optimum level of cement replacement with HCWA for the best compressive strength performance at all curing ages up to 28 days was 8% by total binder weight.…”
Section: Usage Of Wastes In Mortar 1 Binding Materialsmentioning
confidence: 99%
“…Marthong (2012) analysed the hydration characteristics of saw dust ash admixture cement and concluded that 10% addition of wood ash to cement is optimum. High calcium wood ash and densified silica fume blended cement paste was characterized by CheahChee and Mahudin (2011). Chemical analysis of wood ash showed that it has pozzolanic properties (Etiegni and Campbell, 1991).…”
Section: Introductionmentioning
confidence: 99%